Modeling and measurement of precision reducers' efficiency curve - Xu Hang (EDP Sciences, 2021)
Transmission efficiency is the key index when concerning characterizing the performance of precision reducers, and it is usually required to be measured and evaluated. Apart from that, the efficiency value at the rated torque in the efficiency curve is taken as the evaluation value of the efficiency characteristics of precision reducers. However, at present, the research on the efficiency characteristics of precision reducers mainly focuses on theoretical analysis, the development of measurement devices and the measurement methods, while the analysis model of the efficiency curve has not yet been established. In this context, from the perspective of transmission efficiency measurement and evaluation of precision reducers, the efficiency calculation model of precision reducers is established in this paper. Besides, based on the essential change law of the efficiency curve, the efficiency curve analysis model is also set up. To be specific, taking a certain type of RV (rotate vector) reducer as an example, the actual measurement experiments are carried out, and the efficiency curves at different speeds are obtained. The results show that the efficiency of the precision reducer is affected by the measured speed and load torque, and has a positive correlation with the load torque and a negative correlation with the speed. Then, it is proved that the efficiency curve model proposed in this paper can accurately describe the change law followed by the efficiency curve of precision reducers, thus laying a theoretical foundation for the efficiency measurement and evaluation of precision reducers.